A serology conundrum – HIV infection in acute babesiosis infection could merely be a false positive result - Hindosh, Rand; Ernst, Emily; Kamau, James; Cardio, Steven (AL-Kindy College Medical Journal, 2022)
Babesiosis is a tick-borne disease caused by Babesia microti. We present a case of false positive HIV in the setting of confirmed babesiosis infection. An understanding that patients with babesiosis can have a false positive HIV test result is important in management decisions.